Quantitative Determination of 2-Oxo-Imidazole-Containing Dipeptides by High-Performance Liquid Chromatography/Tandem Mass Spectrometry - Somei Komae; Shingo Kasamatsu; Koji Uchida; Hideshi Ihara (Antioxidants, 2022)
2-Oxo-imidazole-containing dipeptides (2-oxo-IDPs), novel imidazole-containing dipeptide (IDP) derivatives, exhibit a much higher antioxidant capacity than that of IDPs. However, quantitative methods have only been developed for IDPs, and methods for the quantitative analysis of 2-oxo-IDPs are needed. In this study, we developed methods for the quantitative analysis of 2-oxo-IDPs by high-performance liquid chromatography with online electrospray ionization-tandem mass spectrometry (HPLC-ESI-MS/MS) coupled with a stable isotope dilution method. First, we prepared stable isotope-labeled IDP and 2-oxo-IDP standards for MS analyses. Next, using these standards, we established highly sensitive, selective, and absolute quantitative analysis methods for five IDPs and five 2-oxo-IDPs by HPLC-ESI-MS/MS, achieving a limit of detection in the fmol range. Finally, we applied the method to various types of meat, such as beef, pork, chicken, and whale meat, demonstrating the detection of both IDPs and 2-oxo-IDPs. Furthermore, we provide the first evidence for the endogenous production of 2-oxo-balenine in meats. The methods developed in this study enable the detection of trace levels of 2-oxo-IDPs in biological samples and could be helpful for understanding the biological relevance of 2-oxo-IDPs.